Art competition announces for African artists (International Library of African Music, 1968)
“AFRICAN ARTS”, a quarterly American magazine devoted to graphic, plastic, performing and literary arts of Africa, has invited high level artists from all over Africa to compete in its 1968 and 1969 competitions.
Keywords: African Music